2006
DOI: 10.1115/1.2218888
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Fluid Dynamics Study of Transitional Flows in Low-Pressure Turbines Under a Wide Range of Operating Conditions

Abstract: A transport equation for the intermittency factor is employed to predict the transitional flows in low-pressure turbines. The intermittent behavior of the transitional flows is taken into account and incorporated into computations by modifying the eddy viscosity, ^t, with the intermittency factor, y. Turbulent quantities are predicted by using Menter's twoequation turbulence model (SST). The intermittency factor is obtained from a transport equation model which can produce both the experimentally observed stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…However, several studies like the ones of Menter et al [11], Langtry et al [12], Kožulović et al [13], and Suzen et al [14] have shown that they can be inefficient, or barely adequate when dealing with flows affected by separationinduced transition mechanisms. A number of approaches have been proposed to address this problem.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies like the ones of Menter et al [11], Langtry et al [12], Kožulović et al [13], and Suzen et al [14] have shown that they can be inefficient, or barely adequate when dealing with flows affected by separationinduced transition mechanisms. A number of approaches have been proposed to address this problem.…”
Section: Introductionmentioning
confidence: 99%
“…It was combined with a turbulence indicator function which switches off the production and destruction terms of the turbulence model if separation is detected and switches these again on if the Mayle-criterion for start of transition in separated state (17) is satisfied. Suzen, Huang et al [74,129,130] used an intermittency equation which is a combination of the equations of Steelant and Dick [83] and Cho and Chung [127]. In their model, the intermittency is a multiplier factor of the eddy viscosity by the SST k-ω turbulence model and is used in the Navier-Stokes equations, but the turbulence equations are not modified.…”
Section: Other Transport Modelsmentioning
confidence: 99%
“…The SST-LR with imposed transition proved superior to the traditional SST with imposed transition in predicting LSB characteristics. As reported by Steelant and Dick [25], Savill [26] found that most low-Reynolds-number turbulence models tend to predict transition too early or too fast.The final method of transition prediction encountered in the literature couples the intermittency ( ), an empirical factor indicating the temporal fraction of turbulent flow during transition, with an algebraic transition onset location and/or transition length correlation [25,[27][28][29][30]. For example, Steelant and Dick [27] followed on the early work by Dhawan and Narasimha [31], and accounted for the growth and transport of turbulent spots via a transport equation for .…”
mentioning
confidence: 99%